The Effects of Seed Infestation by Fusarium proliferatum on Root and Crown Rot, Plant Growth and Phenolic Compounds in Roots of Some Pumpkin (Cucurbita pepo L.) Cultivars - Ebru Sevinç; Nuray Özer (Turkish Journal of Agriculture: Food Science and Technology)
This study investigates the reactions of four summer pumpkin cultivars (cvs. Çağlayan, Mert Bey, Sena Hanım, TG38) to root and crown rot caused by Fusarium proliferatum by taking into account criteria such as disease severity, plant growth (number of leaves, height, dry and fresh weight of shoot) and the accumulation of phenolic compounds in the roots. Seeds of each cultivar were inoculated with the pathogen and left to develop for 1 month at 25oC in a controlled climate room. The content of phenolic compounds in ethanolic root extracts was determined using high-performance liquid chromatography (HPLC). Cv. Sena Hanım had the lowest disease severity (4.40%) among the cultivars, followed by cvs. Çağlayan (10.62%) and Mert Bey (11.07%). Plants developed from inoculated seeds of cvs. Çağlayan and Sena Hanım had no decrease in the number of leaves and in length, fresh and dry weight of shoots in comparison to the control (plants from non-inoculated seeds), while cv. Mert Bey demonstrated a decrease at very low rates in shoot fresh and dry weight (2.24% and 0.77%, respectively). The phenolic compound that exhibited the highest increase in root extracts of cv. Sena Hanım compared to the control among the cultivars was p-coumaric acid (6.57-fold). This study demonstrates that p-coumaric acid can play an important role in the resistance of pumpkin to seed infestation by F. proliferatum.